2018
DOI: 10.26900/jsp.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Research and Diagnosis of Important Painting Methods

Abstract: Both diseases can safely in experimental research need to the histopathological diagnosis many coloring method utilized. This application of Immunohistochemistry and İmmunfloresan coloring methods stands out in terms of definitive diagnosis. Our country and other countries in which research scientists or Diagnostics these methods and which use antibodies to investigate the research planned and many Assembly-style research. İmmunfloresan coloring method, especially of some diseases affecting the immune system, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Some researchers have found that heavy metal salts can cause DNA damage (Fraga et all., 1990;Halliwell et all., 2000;William et all., 2000;Ateş et all., 2004;Burçak et all., 2004;Siomek et all., 2006). Immunohistochemical staining methods are used to detect damage to cells and tissues (Gezen 2017). 8-OHdG was found to be negative in the gastric mucosa of all groups in our study.…”
Section: Discussionmentioning
confidence: 53%
“…Some researchers have found that heavy metal salts can cause DNA damage (Fraga et all., 1990;Halliwell et all., 2000;William et all., 2000;Ateş et all., 2004;Burçak et all., 2004;Siomek et all., 2006). Immunohistochemical staining methods are used to detect damage to cells and tissues (Gezen 2017). 8-OHdG was found to be negative in the gastric mucosa of all groups in our study.…”
Section: Discussionmentioning
confidence: 53%
“…In addition to the findings of other researchers, we have also found that heavy metal salts cause histopathological changes in the stomach. Gezen (2017) stated that immunohistochemical staining methods are used to detect damage to cells and tissues. The positive cells (8-OHdG) were predominantly observed in the areas of active inflammation with prominent cell infiltration (Seki et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have found that heavy metal salts can cause DNA damage (Fraga et al 1990;Halliwell, 2000;Williams et al 2000;Ateş et al 2004;Burçak et al 2004;Siomek et al 2006). Immunohistochemical staining methods are used to detect cell and tissue damage (Gezen, 2017). In this study, we investigated whether or not to produce DNA damage by feeding the carpet shell clam containing heavy metal salts to rats.…”
Section: Discussionmentioning
confidence: 96%